El enseñar/aprender la enfermería comunitaria en la licenciatura - Félix Amézquita, María Araceli (2016)
The present investigation is a qualitative descriptive study, the objectives were: 1. Describe and analyze the teaching / learning of community nursing in nursing undergraduate students of the School of Nursing in Culiacan, Sinaloa, Mexico. 2. Analyze the teaching/learning in the educational process. The theoretical framework was based upon Pedro Demo, Diaz Barriga, Vera Waldow y Vilma de Carvalho. The location was the Nursing Higher School of Culiacan, Sinaloa, Mexico. Teacher and students responded a semi-structured interview. The Ethics principles and scientific criteria were respected. The thematic content analysis was used, emerging three thematics: 1. The individual’s teaching / learning of community nursing. 2. The collective / group teaching / learning of community nursing. 3. Supplemented in practice the individual teaching / learning with the collective/group of community nursing. Final Thoughts: In the current conditions characterized by technological and scientific changes, the individual teaching / learning is important but not sufficient mainly at the community level since it is a space for socialization and interdisciplinary work. Interaction with the "others", teacher and students together, which facilitate s learning both individually and collectively, in addition to taking practice in real settings as spaces for reflection-action is necessary.